The gender perspective in a debate related to the environment and human rights achievement - Giaqueto Gomes, Gabriela [UNESP]; Cristina Canela, Kelly [UNESP] (Centro Universitario La Salle - UNILASALLE, 2021)
This article aims to discuss women role in the socioenvironmental context, in order to demonstrate a dialogue between the historical transformations related to feminine gender and their relationship with the environment. This research analyzes the intersection between environmental sustainability and gender equity, since without social, gender and race equality, a sustainable and fair planet becomes impractical. To support the approach, the two-dimensional Justice Theory is used as a theoretical-philosophical basis, which is defended by the philosopher Nancy Fraser. The article discuss this questions: how to achieve women emancipation within sustainable development context? How to develop spaces of social participation that promotes gender equity and ecological citizenship? The promotion of equality must include women emancipation through an introduction of a gender perspective in policies, and women eff ective participation in environment protection. The research uses the hypothetical-deductive method and bibliographic research.
A perspectiva de gênero no debate relacionado ao meio ambiente e à concretização de direitos humanos
Keywords: Environment; Feminine emancipation; Gender